A clean and efficient utilization of fly ash with a focus on the strengthening decomposition mechanism of mullite. (1st February 2023) - Hao, Jun; Dou, Zhi-he; Zhang, Ting-an; Wang, Kun; Wan, Xing-yuan; Qi, Song
Graphical abstract: Highlights: A low temperature manufacture of ferrosilicon alloying from fly ash was proposed. The notable promoting effect of Fe2 O3 on the decomposition of mullite was verified. The phase transformation in the reduction process of mullite was investigated. A three-step decomposition theory of mullite in fly ash was proposed. Abstract: A novel method of comprehensive disposal of low temperature and high-efficiency reduction of fly ash to produce ferrosilicon without slag under the action of Fe2 O3 was proposed in this paper. In addition, the promotion of Fe2 O3 on the reduction and decomposition of fly ash at a low temperature and the strengthening mechanism of the reduction and decomposition of the mullite phase were systematically studied. The thermodynamic analysis shows that the decomposition reaction of mullite can be carried out only after the free SiO2 in fly ash is exhausted. Combined with the thermodynamic prediction of the equilibrium phase concentration of reduction products, the phase evolution of reduction products and the results of SEM microanalysis, it is proposed that the carbothermal reduction process of fly ash and the decomposition mechanism of mullite are as follows: iron oxide reduction, mullite decomposition into aluminum–silicon oxide and aluminum–silicon oxide deep decomposition and complete release of Al2 O3, while the final products of reduction decomposition are ferrosilicon phase and alumina. According to the mineralogical characteristics of reduction decomposition products, a novel idea of preparing ferrosilicon and alumina/calcium aluminate byproducts by electric furnace melting is proposed, which lays a theoretical foundation for the large-scale, slag-free and high-value utilization of fly ash.